Commensal-Related Changes in the Epidermal Barrier Function Lead to Alterations in the Benzo[ a ]Pyrene Metabolite Profile and Its Distribution in 3D Skin - Lisa Lemoine (American Society for Microbiology, 2021)

(untitled)
Exposure to xenobiotics has repeatedly been associated with adverse health effects. While the majority of reported cases relate to direct substance effects, there is increasing evidence that microbiome-dependent metabolism of xenobiotic substances likewise has direct adverse effects on the host.